Speciation and phylogeography: coalescent-based models applied to the Cape plant genus Pauridia - Rowe, Graham (Department of Biological Sciences, 2023)
The Cape (CFR) is an exceptional centre plant This diversity is concentrated in a profusion geographically restricted endemic species within a The CFR is a rich and dynamic for the molecular study of speciation, but until recently studies have focused on factors influencing diversification of whole lineages, than on details the speciation process within and between species pairs.